Proceedings of the Twenty-Ninth Annual Symposium on Computational Geometry 2013
DOI: 10.1145/2462356.2462399
|View full text |Cite
|
Sign up to set email alerts
|

Ramsey-type results for semi-algebraic relations

Abstract: For natural numbers d and t there exists a positive C such that if F is a family of n C semialgebraic sets in R d of description complexity at most t, then there is a subset F of F of size n such that either every pair of elements in F intersect or the elements of F are pairwise disjoint. This result, which also holds if the intersection relation is replaced by any semi-algebraic relation of bounded description complexity, was proved by Alon, Pach, Pinchasi, Radoičić, and Sharir and improves on a bound of 4 n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…(We defined semilinearity only for graphs, but the definition extends for hypergraphs in a straightforward way.) It was proved by Conlon et al [9] that if H is an r-uniform semialgebraic hypergraph on N vertices of complexity t which contains no clique or independent set of size n, then N ≤ tw r−1 (n C ) for some constant C = C(t), where the tower function tw k (x) is defined as tw 1 (x) := x and tw k+1 (x) := 2 tw k (x) . This bound is also the best possible up to the value of C. Do the Ramsey numbers of r-uniform semilinear hypergraphs behave similarly?…”
Section: Discussionmentioning
confidence: 81%
“…(We defined semilinearity only for graphs, but the definition extends for hypergraphs in a straightforward way.) It was proved by Conlon et al [9] that if H is an r-uniform semialgebraic hypergraph on N vertices of complexity t which contains no clique or independent set of size n, then N ≤ tw r−1 (n C ) for some constant C = C(t), where the tower function tw k (x) is defined as tw 1 (x) := x and tw k+1 (x) := 2 tw k (x) . This bound is also the best possible up to the value of C. Do the Ramsey numbers of r-uniform semilinear hypergraphs behave similarly?…”
Section: Discussionmentioning
confidence: 81%
“…Over the past decade, several authors have shown that many classical theorems in extremal graph theory can be significantly improved if we restrict our attention to semi-algebraic graphs, that is, graphs whose vertices are points in Euclidean space, and edges are defined by a semi-algebraic relation of constant complexity [1,5,8,11,9,4]. In this note, we continue this sequence of works by studying Ramsey-Turán numbers for semi-algebraic graphs.…”
Section: Introductionmentioning
confidence: 88%
“…r (t) denote the smallest N such that any r-uniform semi-algebraic hypergraph of complexity (n, d, m) contains either a clique or an independent set of size t. Conlon et al [13] studied the Ramsey problem for semi-algebraic hypergraphs and proved that there exists c = c(r, n, m, d) > 0 and…”
Section: Ramsey Properties Of Algebraic Hypergraphsmentioning
confidence: 99%